Application of Business Intelligence Using Tableau in Visualizing New Student data - Rizkiawan, M. Asep; Anhari, Tirta; Alim, Endy Sjaiful (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Business Intelligence (BI) has become part of an institution's strategy in formulating, deciding and implementing policies. Of course this is because Business Intelligence (BI) makes it easier to analyze existing data, including in universities such as UHAMKA. This research aims to apply Business Intelligence (BI) using Tableau in visualizing new student data of Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA) in 2023. This research methodology includes several main stages, data collection from UHAMKA's academic information system, data preparation through cleaning and transformation, using Tableau to create interactive visualizations, and analysis of visualization results. The results show that the use of Tableau is able to produce informative and easy-to-understand visualizations, which help in identifying study program preferences, enrollment trends, and demographic profiles of new students. The distribution of new students shows that the S1 Psychology, S1 PGSD, and S1 Management study programs are the top choices, while the D3 Accounting study program has a very low number of applicants. This research concludes that the implementation of BI using Tableau provides significant benefits in the management and analysis of academic data, supports better decision-making, and improves operational efficiency and effectiveness at UHAMKA.